Fc-mediated functions and the treatment of severe respiratory viral infections with passive immunotherapy – a balancing act - Vanderven, Hillary A.; Kent, Stephen J. (Frontiers in Immunology, 2023)
Passive immunotherapies have been used to treat severe respiratory infections for over a century, with convalescent blood products from recovered individuals given to patients with influenza-related pneumonia as long ago as the Spanish flu pandemic. However, passive immunotherapy with convalescent plasma or hyperimmune intravenous immunoglobulin (hIVIG) has not provided unequivocal evidence of a clinical benefit for severe respiratory infections including influenza and COVID-19. Efficacy trials, primarily conducted in latestage disease, have demonstrated inconsistent efficacy and clinical benefit for hIVIG treatment of severe respiratory infections. To date, most serological analyses of convalescent plasma and hIVIG trial samples have focussed on the measurement of neutralizing antibody titres. There is, however, increasing evidence that baseline antibody levels and extraneutralizing antibody functions influence the outcome of passive immunotherapy in humans.In this perspective, findings from convalescent plasma and hIVIG trials for severe influenza, COVID-19 and respiratory syncytial virus (RSV) will be described. Clinical trial results will be discussed in the context of the potential beneficial and deleterious roles of antibodies with Fc-mediated effector functions, with a focus on natural killer cells and antibody-dependent cellular cytotoxicity. Overall, we postulate that treating respiratory viral infections with hIVIG represents a delicate balance between protection and immunopathology.